Synthesis and Antimicrobial Effects of Some Phenylazopropanedinitriles and Their Derivatives - Cete, Servet; Disli, Ali; Yildirir, Yilmaz; Yasar, Ahmet (Asian Journal of Chemistry, 2010)
In this study, phenylazopropanedinitriles and their derivatives were synthesized and their antimicrobial effects were investigated against five different strains of bacteria and yeast. The antimicrobial effects of these compounds were examined at six different doses. It was shown that phenylazopropanedinitriles have an antimicrobial effect on the bacterial and yeast strains within the range 25-1000 μg. Generally, when the dose was increased, the inhibition zone expanded on the growth media. When the phenylazopropanedinitriles are compared with some antibiotics, it is seen that generally these compounds have more antimicrobial effects than some antibiotics.